М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
dianamihalenko9
dianamihalenko9
26.03.2021 14:29 •  Алгебра

Звільніться від ірраціональності в знаменниках дробів:
3/2√6
10/√14-2

👇
Открыть все ответы
Ответ:
Anonim2118
Anonim2118
26.03.2021
y=e ^{2x} -9e ^{x} -2 \\ y'=2e ^{2x} -9e ^{x}=e^x(2e^x-9) \\
Находим нули производной:
eˣ=0    или  2eˣ-9=0

eˣ - не может равняться нулю, так как функция вида у=аˣ всегда больше нуля.
2e^x-9=0 \\ 2e^x=9 \\ e^x=4,5 \\ x=ln4.5

теперь воспользуемся методом интервалов
      -                             +
--------------ln4.5----------------------->

Раз функция меняет знак с минуса на плюс, значит x=ln4.5 - точка минимума.
e≈2.7   ⇒ 
дан промежуток [1;3]
убедимся, что ln4.5 принадлежит данному промежутку:
1=lne
3=3*1=3lne=lne³
e³≈2.7³=19.683
lne<ln4.5<lne³   -  зная, что е>1, знак неравенства сохраняется

e<4.5<e³ - равенство выполняется, значит, действительно ln4.5 принадлежит данному промежутку.

y=e ^{2x} -9e ^{x} -2 \\
 x=1,    y(1)=e² -9e  -2≈2.7²-9*2.7-2=-19.01
x=3,     y(3)=e⁶-9e³-2≈208

x=ln4.5, \ y(ln4.5)=e ^{2ln4.5} -9e ^{ln4.5} -2=(e^{ln4.5} )^{2} -9e ^{ln4.5} -2= \\ =4.5^2-9*4.5-2=-22.25 \\y(ln4.5)\ \textless \ y(1)\ \textless \ y(3) \\ \\ OTBET: -22.25
4,8(30 оценок)
Ответ:
йцукен56
йцукен56
26.03.2021
First, we'll try to plug in the value:
#lim_{x to -oo}x+sqrt(x^2+2x) = -oo + sqrt(oo-oo)#
We're already encountering a problem: it is simply not allowed to have #oo-oo#, it's like dividing by zero.
We need to try a different approach.
Whenever I see this kind of limit, I try to use a trick:
#lim_{x to -oo}x+sqrt(x^2+2x)#
#= lim_{x to -oo}x+sqrt(x^2+2x)*(x-sqrt(x^2+2x))/(x-sqrt(x^2+2x))#
These are the same becaus the factor we're multiplying with is essentially #1#.
Why are we doing this? Because there exists a formula which says: #(a-b)(a+b) = a^2-b^2#
In this case #a = x# and #b = sqrt(x^2+2x)#
Let's apply this formula:
#lim_{x to -oo}(x^2-(sqrt(x^2+2x))^2)/(x-sqrt(x^2+2x))#
#= lim_{x to -oo}(x^2-x^2-2x)/(x-sqrt(x^2+2x))#
#= lim_{x to -oo}(-2x)/(x-sqrt(x^2+2x))#
Now we're going to use another trick. We'r going to use this one, because we want to get the #x^2# out of the square root:
#lim_{x to -oo}(-2x)/(x-sqrt(x^2(1+2/x))#
If you look carefully, you see it's the same thing.
Now, you might say that #sqrt(x^2) = x#, but you have to remember that #x# is a negative number. Because we're taking the positive square root, #sqrt(x^2) = -x# in this case.
#= lim_{x to -oo}(-2x)/(x+xsqrt(1+2/x))#
#= lim_{x to -oo}(-2x)/(x(1+sqrt(1+2/x)))#
We can cancel the #x#:
#= lim_{x to -oo}(-2)/(1+sqrt(1+2/x))#
And now, we can finally plug in the value:
#= -2/(1+sqrt(1+2/-oo))#
A number divided by infinity, is always #0#:
#= -2/(1+sqrt(1+0)) = -2/(1+1) = -2/2 = -1#
This is the final answer.
Hope it helps.
4,7(80 оценок)
Полный доступ к MOGZ
Живи умнее Безлимитный доступ к MOGZ Оформи подписку
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ